Fulfilment of expectations mediating quality and satisfaction: the case of hospital service. (2nd January 2019) - Marimon, Frederic; Gil-Doménech, Dolors; Bastida, Ramon
Abstract : Many attempts have been conducted during the last decades to define a quality measurement scale in the health sector; however, there is not yet a complete agreement on which dimensions impact satisfaction. Besides, a quality scale encompassing all patient concerns related to his/her hospitalisation is still lacking. In this context, the purpose of this study is three aimed: (i) defining a scale ( HospQual ) to assess patients' perceived quality of hospital service; (ii) analysing the impact of perceived quality on patient satisfaction; and (iii) analysing the mediation role of fulfilment of patients' expectations between quality and satisfaction. To capture data regarding Catalan patients' perceived quality of hospital service, two surveys were launched: the first collected 200 questionnaires in June 2016, and the second collected 601 questionnaires in December 2016. An array of exploratory factor analyses was carried out with the first sample to establish the HospQual scale dimensions, which showed appropriate psychometric characteristics. The second sample was used for confirmatory purposes and also to analyse the research model analysis addressed to determine the mediating role of fulfilment of expectations. Findings confirmed HospQual dimensions impact satisfaction. Additionally, fulfilment of expectations is proved to be a mediator between quality and satisfaction.